Biologically relevant arene ruthenium metalla-assemblies. Issue 3 (4th December 2014) - Therrien, Bruno
Abstract : Arene ruthenium complexes have become popular building blocks for the preparation of metalla-assemblies with biological applications, opening a new era for arene ruthenium complexes. Abstract : Arene ruthenium complexes have been known for 50 years and the number of publications involving arene ruthenium complexes has been in constant progression ever since their discovery. Following the synthesis and characterisation of the first arene ruthenium complexes, they have been initially tested as catalysts. Then later on, with the emergence of bio-inorganic chemistry, the biological activity of arene ruthenium complexes was explored. Lately, arene ruthenium complexes have become popular building blocks for the preparation of metalla-assemblies. In this highlight article, we present our contributions in the field of water soluble metalla-assemblies with an emphasis on their biological potentials, revealing that arene ruthenium complexes have found a new playground.